The good wife. The final season [videorecording (DVD)] - Margulies, Julianna, 1966-; Baranski, Christine; Czuchry, Matt, 1977-; Cumming, Alan, 1965-; Noth, Chris, 1954- (CBS DVD ; Paramount, 2016)
As Alicia struggles to get her career back on track, she stumbles on a case that puts her up against Diane Lockhart and David Lee. Peter fires Eli Gold, who vows revenge. Cary discovers that his firm is getting out of touch. Peter has little time left to make a plea deal before the jury comes back with a verdict. Meanwhile, Alicia must decide whether her future is with Peter or with Jason, and she channels the ghost of Will Gardner to help make a decision.